Influence of El Niño and La Niña on sugarcane yield and sucrose production in northern São Paulo, Brazil - Rolim, Glauco de Souza [UNESP]; Caporusso, Natália Buzinaro [UNESP]; Moreto, Victor Brunini [UNESP]; Prela-Pantano, Angélica (My University, 2015)
The El Niño Southern Oscillation (ENSO) influences the global agriculture globally, with complex effects on crop yields in the state of São Paulo in Brazil. We assessed the effects of ENSO on the yield of sugarcane (Saccharum spp.) (tonnes of sugarcane per hectare -TSH) and total recoverable sugar (TRS) at Jaboticabal, one of the most important Brazilian sugarcane producing regions. We determined Pearson linear correlation coefficients monthly and annually to analyze the interactions of TSH and TRS with climatic parameters associated with El Niño (EN), La Niña (LN) and neutrals (NE) years. The annual yield of sugarcane was highly variable, but TSH tended to be higher in NE years, followed by, EN and LN years, and TRS was higher in LN years, followed by NE and EN years. Conditions of the higher soil water storage (STO) and water excess (EXC) led to the higher TSH in NE years. Higher water deficiency (DEF) led to higher TSR in LN years. We developed agrometeorological models to estimate accumulated monthly TSH and TRS for EN, LN and NE years. The models as functions of a thermal index and sum of DEF were accurate for all years, with maximum mean absolute percentage errors of TSH of 12.78 and 8.15% for TSH and TRS, respectively in neutral years.
Keywords: Agrometeorology; ENSO; Model; Total recoverable sugar; Yield